Long-Term Clinical Outcomes of Gastric MALT Lymphoma: A Nationwide Multicenter Study in Korea - Kim, Joon Sung; Park, Jun Chul; Lee, Jong Yeul; Ahn, Ji Yong; Kang, Sun Hyung; Yang, Hyo-Joon; Kim, Su Jin; Joo, Moon Kyung; Park, Jae Myung (Frontiers in Oncology, 2021)
Background: Treatment recommendations for gastric mucosa-associated lymphoid tissue (MALT) lymphoma are based on case series and expert opinions. Only a few previous studies have focused on the long-term outcomes of gastric MALT lymphoma, especially according to stage. Methods: Patients diagnosed with gastric MALT lymphoma from January 2000 to December 2018 at nine university hospitals in Korea were included. Clinical data of medical history, endoscopic features, histological diagnosis, results of Helicobacter pylori (H. pylori) testing, stage, treatment conditions, and outcomes were collected. Results: A total of 1,163 patients was enrolled, and 97.6% (n=1,038) of patients were diagnosed as stage IE. 10-year overall survival (OS) for the entire population was 99.1% and was better for patients in stage IE compared with patients in stage III/IV (p=0.002). The 10-year OS for H. pylori-positive patients was better than that of H. pylori-negative patients (p=0.022). Multivariate analyses revealed initial stage III/IV as a prognostic factor associated with overall survival. Conclusion: The majority of gastric MALT lymphoma patients are diagnosed at an early localized stage in Korea. The overall survival rate of gastric MALT lymphoma is excellent and is associated with the initial stage of the disease.